The Knowledge Management Architecture in Bridging the Gap in Architectural Education and Practice - Taib, Idris; Shukri, Sharyzee Mohmad; Azli , Mohd; A M R, Aminuddin; Aziz, Adrianta; Razak, Ridha (MAJ - Malaysia Architectural Journal, 2024)
The field of architecture practice necessitates a fine balance of theoretical understanding and practical application. The existence of this disparity can hinder the smooth integration of architectural graduates into the industry and restrict their potential to make valuable contributions within the field of architecture. This paper aims to explore knowledge management (KM) architecture to bridge the gap between architectural education and practice. To fill this gap, this research aims to illustrate an overview of all relevant studies on the subject matter. The objective of this research is to identify the potential elements of KM architecture to facilitate the transfer, sharing, and application of knowledge. Secondly, the research examines key elements of KM architecture, including knowledge capture, organization, dissemination, and collaboration. This study's research method is based on a literature review and a questionnaire. The phrases "knowledge management", "architectural education and practice", and "knowledge management framework" were used to search the databases of ScienceDirect, Sage, Frontiers, and PubMed. The data set was restricted to English peer-reviewed academic publications published between 2010 and 2023. The records were then reviewed for relevance and eligibility using predefined inclusion and exclusion criteria. The field of architecture requires a smooth transition from academic learning to practical application, yet there is often a disconnect between the knowledge gained in educational settings and its effective utilization in professional practice. The findings suggest that an effective KM architecture can enhance architectural education by aligning curriculum with industry requirements, integrating real-world case studies and practical experiences, and promoting collaboration between academia and practitioners. In practice, it enables professionals to access relevant knowledge, best practices, and lessons learned from previous projects, leading to improved design outcomes, enhanced efficiency, and increased innovation. This would help in bridging the existing gap between architectural education and practice. Finally, by adopting the KM architecture framework and utilizing appropriate tools as a foundation, the architecture field can efficiently equip aspiring professionals with essential skills while promoting an environment that emphasizes continual learning based on knowledge-driven practices.